2012
DOI: 10.1261/rna.033316.112
|View full text |Cite
|
Sign up to set email alerts
|

Prp2-mediated protein rearrangements at the catalytic core of the spliceosome as revealed by dcFCCS

Abstract: The compositional and conformational changes during catalytic activation of the spliceosome promoted by the DEAH box ATPase Prp2 are only poorly understood. Here, we show by dual-color fluorescence cross-correlation spectroscopy (dcFCCS) that the binding affinity of several proteins is significantly changed during the Prp2-mediated transition of precatalytic B act spliceosomes to catalytically activated B* spliceosomes from Saccharomyces cerevisiae. During this step, several proteins, including the zinc-finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(145 citation statements)
references
References 36 publications
(70 reference statements)
9
135
1
Order By: Relevance
“…In contrast, the majority of Yju2 remained stably associated with the ILS (Table 1). Cwc24 and Cwc27 were not detected in the 35S ILS, consistent with the fact that they dissociate from the spliceosome already during Prp2-mediated catalytic activation of the B act complex (Warkocki et al 2009;Ohrt et al 2012). We note that Cwc23 was not detected by MS either here or in previous studies (Warkocki et al 2009).…”
Section: Protein Composition Of the Isolated 35s Ilssupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast, the majority of Yju2 remained stably associated with the ILS (Table 1). Cwc24 and Cwc27 were not detected in the 35S ILS, consistent with the fact that they dissociate from the spliceosome already during Prp2-mediated catalytic activation of the B act complex (Warkocki et al 2009;Ohrt et al 2012). We note that Cwc23 was not detected by MS either here or in previous studies (Warkocki et al 2009).…”
Section: Protein Composition Of the Isolated 35s Ilssupporting
confidence: 88%
“…For example, we showed recently that catalytic activation mediated by the RNA helicase Prp2 is accompanied by the almost quantitative dissociation of Cwc24 and Cwc27 from the spliceosome (Ohrt et al 2012). Comparison of the protein composition of post-catalytic spliceosomes and the isolated ILS revealed that only a handful of proteins are displaced upon Prp22 action (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We therefore tested whether Snu17p interacts with pre-mRNA in the context of native spliceosomes. Because RES-complex proteins were previously shown to be most abundant and stably bound in activated yeast spliceosomes (B act ) 26,27 , we analyzed whether Snu17p contacts the pre-mRNA in purified B act complexes. To this end, we generated a yeast strain carrying the prp2-1 mutation as well as a C-terminally tandem affinity purification (TAP)-tagged version of Snu17p.…”
Section: Npg a R T I C L E Smentioning
confidence: 99%